Os efeitos do treinamento físico, associado ao perindopril, na rigidez arterial de ratos espontaneamente hipertensos - Miotto, Danyelle Siqueira (Universidade Federal de São Carlos, 2019)
Hypertension (HT) is a complex and multifactorial disease considered one of the main risk factor for cardiovascular diseases. It is maintained mainly by structural changes in vessels that contribute to increase vascular resistance. Changes in the intrinsic elastic properties of the vessel wall contribute to determine arterial stiffness and may compromise vessel functioning. Currently, arterial stiffness has been considered an important predictor of cardiovascular mortality. Among the antihypertensive treatments, angiotensin converting enzyme inhibitors (ACEi) have been used to improve vessel compliance, however, almost nothing is known about the use of ACEi, associated or not with aerobic TF, on the improvement of arterial stiffness in hypertensive animals. We hypothesized that T associated with perindopril could improve arterial stiffness and HT higher than isolated treatments. Therefore, the aim of this study was to investigate the effects of aerobic T, associated or not with perindopril treatment on arterial stiffness, arterial pressure and cardiac remodeling in spontaneously hypertensive rats (SHR). 49 SHR (200-300g) were randomly allocated into 4 groups: 1 / sedentary control (SC, n = 12) 2 / sedentary treated with perindopril (SP, n = 10, 3 mg / kg per day, by gavage) 3 / trained control (TC, n = 13, which underwent treadmill aerobic exercise per 60 days), 4 / trained perindopril (TP, n = 14, which underwent aerobic TF and were treated with perindopril). Ten wistar rats were used as normotensive control. Weekly tail pressure measurements were measured. At the end of experimental protocol, pulse wave velocity (PWV) was performed to analyze arterial stiffness. After measurement of direct arterial pressure (AP), autonomic balance and barroreflex analysis, aorta artery was removed for proteomic analysis and muscle tissues (soleus and left ventricle) for histological analyses. The sedentary hypertensive rats (SC) presented lower body weight (-26.51%) and lower SOL weight (-26%) compared to wistar rats. However, hemodynamic values of SBP, DBP and MAP were elevated (+ 69.61%, 62.33% and 63.53% respectively), as well as VOP (+ 49.35%) and sympathetic nerve activity for vessels (+ 64.33%) when compared to wistar. Spontaneous (non-pharmacological) barroreflex analysis of SC had values of reflex bradycardia (GAIN UP, -43.70%), as well as the sum of reduced reflex bradycardia and reflex tachycardia (GAIN ALL, -42.47%), when compared to wistar. The histological analysis of collagen density was increased (+ 136.80%) in SC rats, whereas C: F (+ 24.34%) was higher in wistar. PWV was higher and treatment with perindopril and / or T were able to reduce it in SHR (-36%, -21% and -46%, for SP, TF and TP, respectively), compared with SC. Media wall AST values were also reduced in the SP (-59%), TC (-55%) and TP (-44%) groups, compared with SC. In addition, LV collagen density was reduced after perindopril (-53%), T (-46%) and its association (-52%). Only trained groups presented higher values of capillary-to-fiber ratio (64% and 37%, for TC and TP respectively). Sympathetic nervous activity to the vessels was also reduced only after T. Proteomic analysis suggested that some proteins that were up regulated after perindopril, were contra balanced by T, through different pathways. Results of this study suggest that reduction of arterial stiffness induced by T maybe associated with renin angiontensin system, since reduction were similar to those after perindopril treatment. Besides functional responses were similar, proteomic results suggest that both strategies act through different protein pathway. Improvements of arterial stiffness may be also associated with local and neural skeletal muscle microcirculation alterationsand both treatments did not determine synergic responses.
Effects of physical training, associated with perindopril, on arterial stiffness of spontaneously hypertensive rats
Keywords: Inibidores da ECA; Velocidade de onda de pulso; Exercício físico; Hipertensão arterial; ACE inhibitors; Pulse wave velocity; Physical training/exercise; Hypertension; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS